Restorative justice and the dangers of community - (:unkn) unknown (My University, 2016)
Though much of what follows may sound like a fundamental criticism of the restorative justice movement, it is not so intended. Rather, it is an admonition to the restorative justice movement about a danger it faces—but that it can beneficially overcome—if it at least remains vigilant in detecting it and self-critical in avoiding it. It is the danger of community.